Endocrine and Metabolic Insights from Pancreatic Surgery. (October 2020) - Mezza, Teresa; Cefalo, Chiara M.A.; Cinti, Francesca; Quero, Giuseppe; Pontecorvi, Alfredo; Alfieri, Sergio; Holst, Jens J.; Giaccari, Andrea
Abstract : Although it is well established that diabetes can also develop as a result of diseases or maneuvers on the exocrine pancreas, the complex relationship between glucose disorders and underlying pancreatic disease is still debated. There is evidence that several features linked to pancreatic diseases can modify endocrine and metabolic conditions before and after surgery. However, pancreatic surgery provides a rare opportunity to correlate in vivo endocrine and metabolic pathways with ex vivo pancreatic samples, to examine the endocrine and metabolic effects of acute islet removal, and finally to clarify the pathogenesis of diabetes. This approach could therefore represent a unique method to shed light on the molecular mechanisms, predicting factors, and metabolic consequences of insulin resistance, islet plasticity, β cell failure, and type 2 diabetes. Highlights: Pancreatic disease can modify endocrine and metabolic homeostasis; however, islet characteristics play a major role in the possible appearance of diabetes. Partial pancreatectomy is an 'accelerator' of declining β cell function rather than the actual cause of diabetes. That is, diabetes appearing after partial pancreatectomy could be better classified as 'accelerated' type 2 diabetes rather than as type 3c. Pancreaticoduodenectomy requires, for anatomical reasons, the removal of 'healthy' tissue from which accurate ex vivo specimens can be obtained. Pancreatic surgery provides a rare opportunity to correlate in vivo endocrine and metabolic pathways (before surgery) with ex vivo data from pancreatic samples. Pancreatic surgery is an excellent model for examining the metabolic and hormonal effects of acute islet removal.